Eksistensi Jurusan Hukum Ekonomi Syariah IAIN Langsa - Zainal Abidin; Agustinar .; Maulina Ulfanur; Rasfadli . (Intiqad: Jurnal Agama dan Pendidikan Islam, 2019)
This study aims to analyze the effect of curriculum, lecturer quality, academic service quality and alumni competence on the existence of Islamic Economics Law Department IAIN Langsa. The population in this study were all alumni of the Islamic Economics Law Department (HES) of Langsa IAIN, while the sample used in this study was that some alumni had worked, so the samples taken were 60 HES IAIN Langsa alumni. The sampling technique used was nonprobability sampling with a type of purposive sampling. The research methodology uses a survey method with a quantitative approach. Data analysis using Multiple Linear Regression analysis using SPSS Version.20 Software. The results of this study indicate that the curriculum (X1) has a positive effect on the existence of the HES Department (Y) with t-values (2,267)> t-table (1.67), then (H1 is accepted). The quality of the Lecturer (X2) has a positive effect on Existence (Y) with a t-value (4.271)> t-table (1.67), then (H2 is accepted). Academic service quality (X3) has a positive effect on the existence of the HES Department (Y) with a t- value (2.886)> t-table (1.67), then (H3 is accepted). Alumni Competence (X4) has a positive effect on Existence (Y) with a t- value (3,920)> t-table (1.67), then (H4 is accepted). Of the several variables that have been tested by lecturer quality which have a dominant influence on the existence of the Islamic Economics Law Department with the resulting t- value of 4.271 which is the highest t-value.